Fixed-dose combination therapies with and without aspirin for primary prevention of cardiovascular disease: an individual participant data meta-analysis. Issue 10306 (25th September 2021) - Joseph, Philip; Roshandel, Gholamreza; Gao, Peggy; Pais, Prem; Lonn, Eva; Xavier, Denis; Avezum, Alvaro; Zhu, Jun; Liu, Lisheng; Sliwa, Karen; Gamra, Habib; Bangdiwala, Shrikant I; et al.
Summary: Background: In randomised controlled trials, fixed-dose combination treatments (or polypills) have been shown to reduce a composite of cardiovascular disease outcomes in primary prevention. However, whether or not aspirin should be included, effects on specific outcomes, and effects in key subgroups are unknown. Methods: We did an individual participant data meta-analysis of large randomised controlled trials (each with ≥1000 participants and ≥2 years of follow-up) of a fixed-dose combination treatment strategy versus control in a primary cardiovascular disease prevention population. We included trials that evaluated a fixed-dose combination strategy of at least two blood pressure lowering agents plus a statin (with or without aspirin), compared with a control strategy (either placebo or usual care). The primary outcome was time to first occurrence of a composite of cardiovascular death, myocardial infarction, stroke, or arterial revascularisation. Additional outcomes included individual cardiovascular outcomes and death from any cause. Outcomes were also evaluated in groups stratified by the inclusion of aspirin in the fixed-dose treatment strategy, and effect sizes were estimated in prespecified subgroups based on risk factors. Kaplan-Meier survival curves and Cox proportional hazard regression models were used to compare strategies. Findings: Three large randomised trials were included in the analysis (TIPS-3, HOPE-3, and PolyIran), with a total of 18 162 participants. Mean age was 63·0 years (SD 7·1), and 9038 (49·8%) participants were female. Estimated 10-year cardiovascular disease risk for the population was 17·7% (8·7). During a median follow-up of 5 years, the primary outcome occurred in 276 (3·0%) participants in the fixed-dose combination strategy group compared with 445 (4·9%) in the control group (hazard ratio 0·62, 95% CI 0·53–0·73, p<0·0001). Reductions were also observed for the separate components of the primary outcome: myocardial infarction (0·52, 0·38–0·70), revascularisation (0·54, 0·36–0·80), stroke (0·59, 0·45–0·78), and cardiovascular death (0·65, 0·52–0·81). Significant reductions in the primary outcome and its components were observed in the analyses of fixed-dose combination strategies with and without aspirin, with greater reductions for strategies including aspirin. Treatment effects were similar at different lipid and blood pressure levels, and in the presence or absence of diabetes, smoking, or obesity. Gastrointestinal bleeding was uncommon but slightly more frequent in the fixed-dose combination strategy with aspirin group versus control (19 [0·4%] vs 11 [0·2%], p=0·15). The frequencies of haemorrhagic stroke (10 [0·2%] vs 15 [0·3%]), fatal bleeding (two [<0·1%] vs four [0·1%]), and peptic ulcer disease (32 [0·7%] vs 34 [0·8%]) were low and did not differ significantly between groups. Dizziness was more common with fixed-dose combination treatment (1060 [11·7%] vs 834 [9·2%], p<0·0001). Interpretation: Fixed-dose combination treatment strategies substantially reduce cardiovascular disease, myocardial infarction, stroke, revascularisation, and cardiovascular death in primary cardiovascular disease prevention. These benefits are consistent irrespective of cardiometabolic risk factors. Funding: Population Health Research Institute.